2022
DOI: 10.3389/fpls.2022.825829
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Nanoparticles Impregnated With Benzenedicarboxylic Acid: A New Approach to Alleviate Combined Stress of DDT and Cadmium in Brassica alboglabra by Modulating Bioacummulation, Antioxidative Machinery and Osmoregulators

Abstract: At present, the alleviation of stress caused by climate change and environmental contaminants is a crucial issue. Dichlorodiphenyltrichloroethane (DDT) is a persistent organic pollutant (POP) and an organochlorine, which causes significant health problems in humans. The stress caused by cadmium (Cd) and the toxicity of DDT have direct effects on the growth and yield of crop plants. Ultimately, the greater uptake and accumulation of DDT by edible plants affects human health by contaminating the food chain. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Under salinity stress, the studies have discovered that bacterially inoculated plants have higher antioxidant enzyme activity (CAT, SOD, POD, and APX) than control plants (Narayanasamy et al, 2020;Kumar et al, 2021). The findings of this study demonstrate that as the concentration of NaCl in rice plants increased, antioxidative enzyme activities like CAT and SOD were also increased (Numan et al, 2018;Mubeen et al, 2022). Increased NaCl content was closely associated with higher antioxidant enzyme activity in rice (Khan et al, 2017;Numan et al, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…Under salinity stress, the studies have discovered that bacterially inoculated plants have higher antioxidant enzyme activity (CAT, SOD, POD, and APX) than control plants (Narayanasamy et al, 2020;Kumar et al, 2021). The findings of this study demonstrate that as the concentration of NaCl in rice plants increased, antioxidative enzyme activities like CAT and SOD were also increased (Numan et al, 2018;Mubeen et al, 2022). Increased NaCl content was closely associated with higher antioxidant enzyme activity in rice (Khan et al, 2017;Numan et al, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…increased the lignin production and activated defense mechanisms and decreased the CAT, SOD, and guaiacol peroxidase level [46]. It was observed that ZnO NPs change into zinc ions which is necessary for metabolic enzymes [52]. Ascorbate peroxidases (APX) scavenge the harmful effect of H 2 O 2 in the plant by utilizing the ascorbic acid and maintain the ROS of chloroplast and other organelles.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident from the literature review that heavy metals cause toxic effects in plants by reducing growth and ultimately leading to their death by impeding various physiological mechanisms of plants (Singh et al, 2016 ; Prerna et al, 2019 ; Mubeen et al, 2022 ). These heavy metals compete with nutrient cations for adsorption, alter the structure and function of plants, produce reactive oxygen species, and disrupt the functions of enzymes (Chaab et al, 2015 ; Ahmad et al, 2021 ; Faiz et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%